Genetic testing and counseling for hypertrophic cardiomyopathy: An evidence‐based practice resource of the National Society of Genetic Counselors. - Miller, Erin M.; Brown, Emily; Christian, Susan; Kelly, Melissa A.; Knight, Linda M.; Saberi, Sara; Rigelsky, Christina; Ingles, Jodie (Journal of Genetic Counseling, 2025)
Hypertrophic cardiomyopathy (HCM) is a common hereditary condition affecting approximately 1 in 500 adults. It is characterized by marked clinical heterogeneity with individuals experiencing minimal to no symptoms, while others may have more severe outcomes including heart failure and sudden cardiac death. Genetic testing for HCM is increasingly available due to advances in DNA sequencing technologies and reduced costs. While a diagnosis of HCM is a well‐supported indication for genetic testing and genetic counseling, incorporation of genetic services into the clinical setting is often limited outside of expert centers. As genetic counseling and testing have become more accessible and convenient, optimal integration of genomic data into the clinical care of individuals with HCM should be instituted, including delivery via genetic counseling. Drawing on recommendations from recent disease guidelines and systematic evidence reviews, we highlight key recommendations for HCM genetic testing and counseling. This practice resource provides a comprehensive framework to guide healthcare providers in the process of genetic test selection, variant classification, and cascade testing for genetic evaluation of HCM.